Peredaran Gelap Narkoba Di Indonesia Pada Masa Pandemi Covid-19 - Nataludin, Christian; Fauziah, Eva; Renel, Rosita Dewi Eka; Ayuningtiyas, Vallendiah (UI Scholars Hub, 2021)
The Covid-19 pandemic caused major changes in health systems and policies related to public health in all countries in the world. UNODC in WDR 2020 said that as for drug markets, the impact of the pandemic is unknown and hard to predict, but various restricted activities had affected demand in the market, the price, and the quality of drugs. This study aims to see how the impacts of Covid-19 pandemic on the problem of illicit drug trafficking, the pattern, and the modus of illicit drug trafficking in Indonesia. The research method used in this research is descriptive qualitative through a library approach. Result of this research showed that the illicit drug trafficking in Indonesia can be said to be less affected by the Covid-19 pandemic.. The decline in drug trafficking in Indonesia was only seen in the first and second quarters of the Covid-19 pandemic. Then the convergence of drugs into a dangerous addictive substance is also possible in Indonesia if it is seen significantly from the significant amount of evidence confiscated by benzodiazepines and tramadol. In addition to being wary of drug trafficking which starting to return to pre-pandemic conditions and even increasing, it is also necessary to be aware of new modus of illicit drug trafficking in Indonesia through the internet and social media. Keywords: Covid-19, Narcotics, Drugs, Illicit Drugs Trafficking, Pandemic